Hepatic and renal function impact concentrations of plasma biomarkers of neuropathology. Issue 1 (12th July 2022) - Berry, Kacey; Asken, Breton M.; Grab, Joshua D.; Chan, Brandon; Lario Lago, Argentina; Wong, Randi; Seetharaman, Srilakshmi; LaHue, Sara C.; Possin, Katherine L.; Rojas, Julio C.; Kramer, Joel H.; Boxer, Adam L.; et al.
Abstract: Introduction: The impact of hepatorenal function on plasma biomarkers of neuropathology is unknown. Herein, we measured several plasma biomarkers in patients with cirrhosis. Methods: Plasma phosphorylated tau (p‐tau181), neurofilament light chain (NfL), glial fibrillary acidic protein (GFAP), total tau (t‐tau), and ubiquitin carboxyl‐terminal hydrolase L1 (UCHL1) were measured in 135 adults with cirrhosis and 22 healthy controls using Simoa. Within cirrhosis, associations between biomarkers and hepatorenal function were explored using linear regression. Results: p‐tau181, NfL, t‐tau, and UCHL1 were increased 2‐ to 4‐fold in cirrhosis, whereas GFAP was not increased. Within cirrhosis, creatinine moderately correlated with p‐tau181 ( β = 0.75, P < .01), NfL ( β = 0.32, P < .01), and t‐tau ( β = 0.31, P < .01), but not GFAP ( β = –0.01, P = .88) or UCHL1 ( β = –0.05, P = .60), whereas albumin showed weak, inverse correlations: p‐tau181 ( β = –0.18, P < .01), NfL ( β = –0.22, P < .01), GFAP ( β = –0.17, P < .05), t‐tau ( β = –0.20, P = .02), and UCHL1 ( β = –0.15, P = .09). Conclusions: Elevated p‐tau181, NfL, and t‐tau in cirrhosis were associated with renal impairment and hypoalbuminemia, suggesting that hepatorenal function may be important when interpreting plasma biomarkers of neuropathology.